AKSEPTABILITAS, UTILISASI DAN ADOPSI UPAYA PENANGGULANGAN HIV MELALUI KADER DESA PEDULI AIDS DARI PERSPEKTIF MASYARAKAT DI KOTA DENPASAR - Ni Made Sri Nopiyani; Desak Putu Yuli Kurniati; Putu Ayu Indrayathi; Rina Listryowati (Program Studi Sarjana Kesehatan Masyarakat Universitas Udayana Berasosiasi Dengan Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI), 2013)
Village AIDS Cadres (KDPA) Program has been conducted in Denpasar district since 2010. Despite the importance of community participation for a successful community based program, no research has been conducted to explore community perception regarding KDPA program.This research is aimed to explore community perceptions regarding acceptability, utilization, and adoption of the KDPA program from community perspective.The design used in this research is descriptive with qualitative data collection method through six focus group discussions in six villages in Denpasar. Data was analysed using thematic analysis.KDPA is well-accepted as it is perceived as an important issue to be tackled in the community. However, many opinions arise concerning who should be given the role